If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -5y = 33 + -5x Solving 3x + -5y = 33 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 3x + 5x + -5y = 33 + -5x + 5x Combine like terms: 3x + 5x = 8x 8x + -5y = 33 + -5x + 5x Combine like terms: -5x + 5x = 0 8x + -5y = 33 + 0 8x + -5y = 33 Add '5y' to each side of the equation. 8x + -5y + 5y = 33 + 5y Combine like terms: -5y + 5y = 0 8x + 0 = 33 + 5y 8x = 33 + 5y Divide each side by '8'. x = 4.125 + 0.625y Simplifying x = 4.125 + 0.625y
| -16x-3y=12 | | 27w=-3w | | 456c=4 | | -15+5a=6a | | 10+x=5(x)+40 | | W-13.2=10.4 | | f(-6x)=6x^2-4 | | (3n+5)(n-2)-3n(n+1)=6 | | G-72=36 | | -14-63-(-52)= | | 4x-2-4= | | -6-6p+-1= | | -2(-7x+3)+3x=8x-15 | | 27th=-3w | | log^3(3x+8)=log^3(x^2+x) | | 3x-24+x=180 | | 2n^2+2n=4 | | 0.05x+0.09(10000-1x)=240 | | 4y=-1x+5 | | 87-(-34)+13= | | 3/5*5/6= | | 3(x-8)=2(3x+21) | | 67+20x=-3+15x | | 4x+8=2x+54 | | X-12=y+7 | | 2(-3/4x-3/4) | | 9b(2b+5)+4b(6b+6)= | | 8+12n-6=9n+56-6n | | 4x+30+9x+42=104 | | 180=2(2x+2)+3x+1 | | -3x-8(16)=-2 | | (5/4)4/5x=36(5/4) |